Inhibition of Hydrogen Sulfide Production by Gene Silencing Attenuates Inflammatory Activity by Downregulation of NF-κB and MAP Kinase Activity in LPS-Activated RAW 264.7 Cells. (18th August 2014) - Badiei, Alireza; Muniraj, Nethaji; Chambers, Stephen; Bhatia, Madhav
Abstract : Hydrogen sulfide is an endogenous inflammatory mediator produced by the activity of cystathionine γ -lyase (CSE) in macrophages. The objective of this study was to explore the mechanism by which hydrogen sulfide acts as an inflammatory mediator in lipopolysaccharide- (LPS-) induced macrophages. In this study, we used small interfering RNA (siRNA) to inhibit CSE expression in macrophages. We found that CSE silencing siRNA could reduce the LPS-induced activation of transcription factor nuclear factor- κ B (NF- κ B) significantly. Phosphorylation and activation of extra cellular signal-regulated kinase 1/2 (ERK1/2) increased in LPS-induced macrophages. We showed that phosphorylation of ERK in LPS-induced RAW 264.7 cells reached a peak 30 min after activation. Our findings show that silencing CSE gene by siRNA reduces phosphorylation and activation of ERK1/2 in LPS-induced RAW 264.7 cells. These findings suggest that siRNA reduces the inflammatory effects of hydrogen sulfide through the ERK-NF- κ B signalling pathway and hydrogen sulfide plays its inflammatory role through ERK-NF- κ B pathway in these cells.